Morphosyntactic production and processing skills in relation to age effects and lexical-phonological levels among children with cochlear implants and typically hearing peers: a focus on vowel nasality - Fagniart, Sophie; Charlier, Brigitte; Delvaux, Véronique; Harmegnies, Bernard Georges; Huberlant, Anne; Piccaluga, Myriam; Huet, Kathy (Frontiers in Human Neuroscience, 2025)
IntroductionSignificant variability in the language performance of children with cochlear implant (CI) is widely recognized in the literature, particularly concerning morphosyntactic (MS) skills. The perceptual limitations of the CI, which can lead to phonological difficulties, may be responsible for this increased vulnerability in grammatical abilities. In this context, the present study focuses on the morphophonemic processing of items distinguished by nasal and oral vowels in the French language – the feature of vowel nasality being known as challenging for the CI population. Links between these performances with chronological/auditory ages and phonological and grammatical production skills will also be explored.MethodNineteen children with CIs and 47 children with typical hearing (TH) were assessed for phonological skills through a picture-naming task, perceptual skills through a task involving the sentence/word-picture matching task with word target containing nasal vs. oral vowels, and morphosyntactic production skills through narrative productions. Various measures of linguistic complexity [Mean Length of Utterance (MLU), verbs/utterances (V/U)] and lexical diversity (D index) were evaluated among our groups and linked to perceptual and productive phonological performances. Chronological and auditory ages as well as phonological accuracy and vocabulary levels as been studied as covariates.ResultsChildren with CIs displayed significantly lower morphosyntactic (MS) performance compared to peers with TH of the same chronological age, particularly in measures such as MLU in morphemes, complexity of function words, and processing of morphemes carried by nasal and oral vowels. However, when controlling for auditory age or phonological/lexical levels, these differences were no longer significant, suggesting a potential for compensation when similar auditory or linguistic experiences are achieved. Despite this, CI users showed distinct patterns of function word use, with fewer complex forms and more frequent errors, likely reflecting the perceptual challenges linked to CI. Additionally, a specific strong relationship between MS skills and phonological accuracy was observed in the CI group, potentially accounting for the marked inter-individual variability in MS development.ConclusionThe perceptual limitations of the CI have a significant impact on the linguistic development of children with CI and contribute to the widely documented variability in performance.